PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) TENTANG PERSAMAAN LINEAR SATU VARIABEL DI SMP NEGERI 14 KOTA BOGOR - Ineu Heryati (Universitas Pakuan, 2021)
IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE APPLICATION OF DISCOVERY LEARNING MODELS ABOUT ONE VARIABLE LINEAR EQUATIONS IN JUNIOR HIGH SCHOOL (SMP NEGERI 14 KOTA BOGOR)The research departs from the phenomenon that occurs in the classroom that the low quality of learning Mathematics can have an influence on student learning outcomes. Therefore, a teacher needs to consider a learning model that is in accordance with the learning material so that it can improve student learning outcomes. One of the learning models tested through this research is the Discovery Learning model. The study was conducted in class 7D of Junior High School (SMP Negeri 14 Bogor City) Semester I of the 2019/2020 Academic Year, with the aim of (1) knowing that the discovery learning model can improve student learning outcomes about linear equations of one variable, ( 2) describe the process of improving student learning outcomes about one variable linear equation after applying the discovery learning model, (3) measuring the magnitude of the increase in student learning outcomes about one variable linear equation after applying the discovery learning model. The results of this study indicate that the application of the Discovery Learning learning model about the linear equation of one variable in the 7D class of Junior High School (SMP Negeri 14 Bogor City) before applying the Discovery Learning learning model has an average value of 69.41. When the learning was changed by applying the Discovery Learning learning model, the average student learning outcomes increased to 77.06 in the first cycle and 85.53 in the second cycle. From the description above, the researcher concludes that the application of the Discovery Learning learning model used by the teacher can improve student learning outcomes, therefore the researcher suggests that the application of the Discovery Learning learning model needs to be socialized and used in learning Mathematics in schools within the Bogor City Education Office.